2010
DOI: 10.1021/jm1000024
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent β-Carbolines as Potential Multitarget Anti-Alzheimer Agents

Abstract: Alzheimer's disease (AD) is a prevalent neurodegenerative disorder with multifactorial causes that requires multitargeted treatment. Inhibitors of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) improve cholinergic signaling in the central nervous system and thus AChE inhibitors are well established in the therapy of AD to improve memory disturbances and other cognitive symptoms. On the other hand, AD patients benefit from reduction of pathologic glutamate-induced, Ca(2+)-mediated excitotoxicity b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(81 citation statements)
references
References 37 publications
3
78
0
Order By: Relevance
“…80 Bivalent β-carboline compound blocked AChE as well as the [Ca 2+ ] c transients elicited by glutamate by inhibiting NMDARs. 81 Destabilization of microctubules through tau hyperphosphorylation distorts axonal transport and contributes to neuronal death in AD. 82 Such hyperphosphorylation is carried out by various kinases, i.e.…”
Section: Acs Chemical Neurosciencementioning
confidence: 99%
“…80 Bivalent β-carboline compound blocked AChE as well as the [Ca 2+ ] c transients elicited by glutamate by inhibiting NMDARs. 81 Destabilization of microctubules through tau hyperphosphorylation distorts axonal transport and contributes to neuronal death in AD. 82 Such hyperphosphorylation is carried out by various kinases, i.e.…”
Section: Acs Chemical Neurosciencementioning
confidence: 99%
“…Despite previous studies having already reported on dual AChE/NMDAR compounds [28,29], this was the first time that two marketed drugs were rationally combined in a single new chemical entity.…”
Section: Development Of Memantine-galantamine Hybrids Via a Linking Smentioning
confidence: 92%
“…Different concentrations of the test compounds 25 and cis-32 were added 30 min before addition of (S)-glutamate and glycine and the released amount of LDH was measured. 36 In Figure 2 the inhibition of glutamate/glycine induced excitotoxicity at different concentrations of phenols 25, cis-32 and methyl ether 2a is compared. The phenylbutyl derivative 25 reduced the excitotoxicity with an IC 50 -value of 18.4 nM.…”
Section: Functional Activitymentioning
confidence: 99%